The Impact of Unemployment, Human Development Index and Internet Penetration on Income Inequality: Evidence from the Sulawesi Region, Indonesia - Hasbiullah; Muhammad Febriansyah; Baso Iwang; Virginia Nuraulia Syah Rasyid (Faculty of Economics, Universitas Sriwijaya, 2025)
This study examines the impact of unemployment, the Human Development Index (HDI), and internet penetration on income inequality in six provinces of the Sulawesi region during 2019–2023. Inclusive development remains a central pillar of Indonesia’s strategy to achieve the Sustainable Development Goals (SDGs) by 2030. Nevertheless, income inequality continues to pose serious challenges, particularly in Sulawesi, where several provinces record relatively high Gini ratios. Using panel data regression with a two-way fixed effects model, the results indicate that unemployment and HDI have negative but statistically insignificant effects on income inequality, while internet penetration is associated with a significant reduction in inequality. Jointly, the explanatory variables are statistically significant, suggesting that these factors collectively play an important role in shaping income inequality in the Sulawesi region. The findings highlight the importance of digital inclusion, alongside improvements in human development and labor market conditions, in fostering more balanced and inclusive regional economic growth in Indonesia.